Composition for forming a low dielectric loss molded article, molded article forming method, and low dielectric loss molded article
Patent Information
- Application Number
- CN202580021292.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-15
- Filing Date
- 2025-03-14
- Publication Date
- 2026-10-16
AI Technical Summary
因此,该文献中描述的技术是不利的,因为它与用于大规模生产的技术(例如挤出成型)不相容,并且需要额外的固化步骤
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to compositions for forming molded products, molded products obtained therefrom, and methods for forming molded products using the compositions. The compositions and molded products obtained therefrom are characterized by low dielectric loss in the millimeter wavelength range, making them suitable for applications such as radar radomes. Background Technology
[0002] Molded articles are used in a wide variety of applications and are formed from a large number of possible compositions, typically based on thermoplastic polymers such as polyethylene, polypropylene, polyesters such as PET, polyamides, polystyrene, etc., including homopolymers and copolymers. Furthermore, preparation methods are widely known, and examples include injection molding, blow molding, extrusion molding, thermoforming, compression molding, rotational molding, etc.
[0003] However, all polymers have limitations in certain properties, such as chemical resistance, transparency to visible light and other wavelengths of electromagnetic radiation, dimensional stability, processability, and hardness. Finding a material that provides a suitable balance of properties for a given application is often challenging, and the desired balance can usually only be achieved by using certain additives or by using polymer blends. Given the vast variety of polymers and additives, the number of possible combinations is essentially unlimited.
[0004] While durability and toughness are critical requirements for many applications, some applications demand additional performance, such as low-loss dielectric properties. Dielectric loss, also known as the dielectric loss factor or tanδ (tan delta), is a measure of the energy lost as heat when a dielectric material is subjected to an alternating electric field. When an alternating voltage is applied to a dielectric material, the electric dipoles within the material attempt to align themselves with the changing electric field. This alignment process is not instantaneous; the dipoles require some time to respond to the alternating field. This alignment delay causes the dielectric material to absorb energy, and a portion of this absorbed energy is subsequently lost as heat due to various factors, including molecular friction and interfacial effects. Dielectric loss is characterized by the dielectric loss angle (tanδ), which is the tangent of the phase angle difference between the applied alternating electric field and the polarization generated within the material. Mathematically, it can be expressed as... Complex permittivity takes into account both the real (energy storage) and imaginary (loss) components of the dielectric constant. High dielectric loss is undesirable in many applications, especially in capacitors and insulating materials, as it leads to energy dissipation and can cause the material to heat up. Therefore, materials with low dielectric loss are preferred in applications where efficient energy storage or insulation is critical (e.g., in electronic equipment and power distribution systems).
[0005] It is important to note that the dielectric loss of a material is frequency-dependent; different dielectric materials exhibit varying degrees of dielectric loss at different frequencies. Therefore, a material exhibiting low dielectric loss at a given frequency in a particular application may not be suitable for another application where the electromagnetic waves encountered have different frequencies.
[0006] Molded articles have been used in a variety of devices that rely on electromagnetic radiation, including, for example, radar equipment. Radar equipment used in vehicles such as cars and trucks typically operates in the millimeter-wave frequency range. The two main frequency bands for automotive radar applications are the 24 GHz and 76-81 GHz bands. Therefore, low dielectric loss is required in this wavelength region for radar radomes (structural weatherproof enclosures, covers, or housings that protect radar antennas).
[0007] Currently, plastic materials used to manufacture radomes include ABS, polycarbonate, Kydex® 8482, Noryl™ (available from Curbell Plastics), PEEK, PTFE, PE, polyurethane foam, and polyesters such as PBT (polybutylene terephthalate), which can also be blended with reinforcing materials such as glass fiber. However, some of these materials require specific processing steps and are incompatible with technologies such as extrusion molding, while others lack sufficient transparency (excessive dielectric loss) at the radar wavelengths used, thus limiting the operating range of radar equipment.
[0008] For automotive short-range radar applications entering the millimeter wavelength range, currently available thermoplastic materials used as radome materials do not meet all future challenges and requirements in terms of mechanical stability and low dielectric loss to extend the operating range of radar sensors. Specifically, there is a need for thermoplastic materials with low dielectric loss (df) and dielectric constant (dk), stable over a wide temperature and frequency range, while also possessing high mechanical stability and dimensional tolerances to avoid negative mechanical effects such as warping after injection molding. Based on the final assembly process, this new material may also need to be laser-weldable and require low water / moisture absorption. Needless to say, for a laser-weldable material, it must be able to absorb at least a portion of the laser radiation and convert it into heat; that is, significant dielectric loss is required at the laser wavelength to heat the material and allow welding.
[0009] WO 2001 / 074146 A1 describes a polybutylene terephthalate composition comprising (A) a polybutylene terephthalate (PBT) resin, (B) a polyester copolymer having a melting point of 105°C to 185°C, (C) a vinyl-based polymer, and optionally (D) hollow glass microspheres. This composition is intended for high-frequency applications, such as mobile phones and mobile communication devices.
[0010] WO 2018 / 151800 A2 relates to a radome material comprising a low-viscosity cyclic olefin resin. The technique described herein is said to produce radomes with low dielectric constant, low loss tangent, low hygroscopicity, lightweight, and tensile strength. This document relies on a complex vacuum-assisted resin transfer method (VARTM), uses a cyclic olefin resin as a layer material, and requires a substrate such as a fiberglass mat or nonwoven fabric, onto which the resin is deposited or impregnated, followed by curing. Therefore, the technique described in this document is disadvantageous because it is incompatible with techniques used for large-scale production, such as extrusion molding, and requires additional curing steps. Furthermore, the need for a substrate and additional layers increases thickness, weight, and cost, and complicates the manufacture of the radome. Summary of the Invention
[0011] Technical issues The present invention therefore aims to provide materials suitable for producing molded parts, methods for producing molded parts, and molded parts obtained therefrom, which exhibit one or more of the following, preferably more than one, and more preferably all of them: - It has low dielectric loss at the operating wavelength of radar equipment; - Laser weldability; - Sufficiently high mechanical toughness and durability; - Through processability of molding technologies (especially injection molding) suitable for mass production; - Prevents or reduces the occurrence of warping; - No additional curing step is required; - No additional layers and / or substrates are required, which allows for the manufacture of radar radomes with reduced thickness (which in turn allows for lower cost and weight). - Provides the ability to optimize thickness to reduce or minimize radar frequency distortion and absorption, as expressed in dB loss.
[0012] Solution to the problem The inventors have conducted diligent research and discovered that the above-mentioned problems can be solved by the following implementation methods: 1. A composition for forming a molded article, comprising: A thermoplastic adhesive phase, and, dispersed in the thermoplastic adhesive phase B. At least one material capable of reducing the dielectric constant and dielectric loss of the composition. The thermoplastic adhesive phase includes at least: A.1 One or more cyclic olefin copolymers, and A.2 Thermoplastic materials other than cyclic olefin copolymers, preferably selected from polyesters, polyolefins, especially homopolymers of ethylene, homopolymers of propylene and copolymers of ethylene or propylene with other α-olefins, polyamides, polycarbonates, polystyrene, copolymers of styrene such as ABS, SAN and SB, acrylic polymers, polyethersulfone, polyetheretherketone, polyetherimide, polyphenylene ether, polyphenylene sulfide, and melt-processed fluorinated polymers such as PVDF or PTFE. The amount of material B, which can reduce the dielectric constant and dielectric loss of the composition, is 5% by weight or more relative to the total weight of the composition. The total amount of one or more cyclic olefin copolymers is 10 to 95% of the total weight of thermoplastic binder phase A.
[0013] 2. The composition for forming a molded article according to Embodiment 1, wherein B, a material capable of reducing the dielectric constant and dielectric loss of the composition, includes one or more of the following: B.1 Glass fiber; B.2 Hollow glass spheres; and B.3 Aerogel; And preferably includes both B.1 glass fiber and B.2 hollow glass spheres.
[0014] 3. The composition for forming a molded article according to embodiment 1 or 2, wherein the thermoplastic binder phase further comprises, in addition to components A.1 and A.2 A.3 One or more impact modifiers, which may or may not have a core-shell structure, preferably selected from styrene block copolymers (SBCs), such as styrene-ethylene-butene-styrene block copolymers (SEBS), methyl methacrylate-butadiene-styrene (MBS), acrylonitrile-butadiene-styrene (ABS); acrylic impact modifiers (AIMs), such as acrylate-methacrylate copolymers, acrylonitrile-styrene-acrylates (ASA), ethylene-propylene-diene monomer (EPDM) copolymers, chlorinated polyethylene (CPE), ethylene-vinyl acetate copolymers (EVA), acrylonitrile-butadiene rubber (NBR), maleic anhydride modified polymers such as maleic anhydride-grafted EPDM and maleic anhydride-grafted ethylene / C3-12 α-olefin copolymers, ethylene-unsaturated epoxide copolymers, ethylene-carboxylic anhydride copolymers, polymers made from hydroxyl-functional monomers, such as polymers comprising repeating units derived from (meth)acrylate hydroxyl C2-6 alkyl esters; and combinations thereof; The impact modifier is present in an amount of 0.1 to 10% by weight of the total weight of thermoplastic binder phase A.
[0015] 4. The composition for forming a molded article according to embodiment 1, 2 or 3, wherein the composition satisfies one or more of the following: (a) Density: 1.30 g / cm³ 3 or smaller (b) Dielectric constant at 76.5 GHz: 2.58 or less (c) Dielectric loss at 76.5 GHz: 0.01 or less (d) Transmittance at 980 nm: 8% or more.
[0016] 5. The composition for forming a molded article according to any one of embodiments 1 to 4, wherein the thermoplastic material other than the cyclic olefin copolymer is selected from polyolefins and polyesters, wherein the polyester is preferably polyalkylene terephthalate, more preferably polybutylene terephthalate, and wherein preferably, the thermoplastic material other than the cyclic olefin copolymer selected from polyolefins and polyesters is present in an amount of 30 to 65% by weight of the total composition.
[0017] 6. The composition for forming a molded article according to any one of embodiments 1 to 5, wherein the amount of the cyclic olefin copolymer is 10 to 85% by weight of the total composition, preferably 15 to 60% by weight.
[0018] 7. The composition for forming a molded article according to any one of embodiments 1 to 6, wherein the cyclic olefin copolymer is a copolymer composed of repeating units derived from ethylene and one or more cyclic olefins, wherein the cyclic olefin is preferably norbornene or a norbornene derivative, preferably 2-norbornene.
[0019] 8. The composition for forming a molded article according to Embodiment 7, wherein the content of norbornene or a norbornene derivative, preferably 2-norbornene, is 45 mol% or more, preferably 50 mol% or more, of all repeating units of the copolymer of ethylene and cyclic olefins.
[0020] 9. A composition for forming a molded article according to any one of embodiments 1 to 8, comprising glass fiber and hollow glass spheres as component B, and satisfying the following relative amounts of components in weight % relative to the total weight of the composition: A thermoplastic adhesive phase of 60 to 90, preferably 70 to 80. B.1 Glass fiber 5 to 20, preferably 10 to 15 B.2 Hollow glass spheres: 5 to 20, preferably 10 to 15.
[0021] 10. The composition for forming a molded article according to Embodiment 9, wherein the thermoplastic binder phase comprises, by weight percent relative to the total weight of the binder phase: A.1 Cyclic olefin copolymers 15 to 75 A.2 Polyalkylene terephthalate 25 to 85 A.3 Impact modifier 0 to 20.
[0022] 11. A composition for forming a molded article according to any one of embodiments 1 to 7, wherein component B comprises B.3 one or more aerogels, wherein the aerogel is preferably selected from silica and polymer aerogels, such as aerogels obtained from polyimide, and / or wherein the aerogel preferably has a porosity of 90% or greater.
[0023] 12. The composition for forming a molded article according to any one of embodiments 1 to 11, wherein the glass forming the glass fibers and / or hollow glass spheres has a dielectric constant of 6.5 (at 1 MHz) or less.
[0024] 13. The composition for forming a molded article according to any one of embodiments 1 to 12, wherein... A.1 is a cyclic olefin copolymer based on ethylene and norbornene. A.2 is polybutylene terephthalate, and B represents glass fiber and hollow glass spheres.
[0025] 14. The composition for forming a molded article according to any one of embodiments 1 to 13, The thermoplastic adhesive phase includes A.1 and A.2, and optionally includes A.3. A.1 is a cyclic olefin copolymer based on ethylene and norbornene. A.2 is polybutylene terephthalate, and A.3 is an impact modifier. B is made of glass fiber and hollow glass spheres, and in The amounts of A.1, A.2, and A.3, expressed as a percentage by weight relative to the total weight of the binder phase, are as follows: A.1 is 15 to 75% by weight. A.2 is 25 to 85% by weight, and A.3 is 0 to 20% by weight, and B is a material that can reduce the dielectric constant and dielectric loss of the composition in an amount of 15 to 20% by weight or more relative to the total weight of the composition.
[0026] 15. A molded part which can be obtained from the composition according to any one of embodiments 1 to 14.
[0027] 16. The molded part according to embodiment 15 is an antenna radome or housing for an electronic device, preferably a device that emits and / or receives radiation in the range of 5 MHz to 130 GHz.
[0028] 17. The molded part according to embodiment 16, wherein the radome or housing is part of the radar equipment of a vehicle, preferably an automobile or truck.
[0029] 18. A method for manufacturing a molded part according to embodiment 15 or 16, comprising processing the composition according to any one of embodiments 1 to 14 by extrusion molding and / or laser welding.
[0030] 19. Use of the composition as defined in any one of embodiments 1 to 14 for manufacturing a housing or radome of an electronic device, preferably a device for emitting and / or receiving radiation in the range of 5 MHz to 130 GHz, more preferably a radar device.
[0031] 20. An electrical or electronic device for transmitting and / or receiving electromagnetic radiation in the range of 5 MHz to 130 GHz, the device comprising a housing or radome made of a composition as defined in any one of embodiments 1 to 12, or a molded part according to embodiment 13 or 14.
[0032] 21. The electrical or electronic equipment according to embodiment 20 is a radar device for a vehicle, preferably a car or truck. Detailed Implementation
[0033] The following definitions are used to interpret the meaning of the terms discussed in the specification and stated in the claims.
[0034] As used in this article, the indefinite article “one” indicates one or more, and does not necessarily restrict the noun it refers to to be singular.
[0035] As used herein, the term "about" means that the quantity or value under discussion can be the specified particular value or some other value nearby. Generally, the term "about" to indicate a value is intended to represent a range within ±5% of that value. As an example, the phrase "about 100" means a range of 100 ± 5, that is, a range of 95 to 105. Generally, when using the term "about," it is expected that similar results or effects according to the invention can be obtained within ±5% of the indicated value.
[0036] As used herein, the term “and / or” means that all or only one element of the group may be present. For example, “A and / or B” should mean “A only, or B only, or both A and B”. In the case of “A only”, the term also covers the case where B is not present, i.e., “A only, but not including B”.
[0037] The term "at least partially" is intended to indicate that the following performance is satisfied to some extent or completely. Preferably, the term indicates that the following performance is satisfied by at least 50% or more, more preferably at least 75%, and even more preferably at least 90%. Preferably, the term can mean "completely".
[0038] The terms “substantially” and “basically” are used to indicate that a feature, performance, or parameter is fully (in its entirety) or substantially satisfied, where substantially means that the difference between the feature, performance, or parameter and full satisfaction is such that the difference does not adversely affect the expected result. Therefore, depending on the circumstances, the terms “substantially” or “basically” preferably mean, for example, at least 80%, at least 90%, at least 95%, or 100%.
[0039] The term "comprising" as used herein is intended to be non-exclusive and open-ended. Thus, a composition comprising, for example, compound A may include other compounds besides compound A. However, the term "comprising" also encompasses the more restrictive meanings of "consistently composed of" and "composed of," such that, for example, a "coating composition comprising compound A" may also consist (substantially) compound A.
[0040] The term "at least one" has the same meaning as "one or more," and therefore implies that more than one compound may be present in the indicated class. The term "at least one" thus covers the exact value of 1, but also covers 2, 3, 4 or more.
[0041] The ranges given below include the upper and lower limits and any values in between. For example, the range "1 to 10" includes the values 1 and 10, and any values in between, such as 2, 2.5, 4.7, or 8.3.
[0042] In some aspects, the claimed subject matter can be characterized by physical properties such as dielectric constant or dielectric loss at an indicated frequency, such as 76.5 GHz, which are typically defined numerically. These values should be determined by test methods commonly used in the art or by the test methods described in the following detailed description (including examples). When different test methods produce different results, the test methods indicated in the specification shall prevail. If there is a difference between the general description and the methods used in the examples, the methods in the examples shall prevail.
[0043] Unless otherwise specified, all physical properties should be determined at standard pressure (1 atm) and room temperature (25°C).
[0044] Unless otherwise specified, the dielectric constant and dielectric loss refer to values at 76.5 GHz, and their respective values can be determined according to VDM 288 (09 / 2023).
[0045] Unless otherwise specified, the density of a material (e.g., a polymer material) can be determined by displacement methods, such as those specified in ASTM D792-20.
[0046] The transmittance of plastic materials at a given wavelength can be determined according to ASTM D1003-21.
[0047] In this invention, the term "molded article" is equivalent to "molded product".
[0048] Composition The compositions of the present invention for forming molded articles and their components will be described below.
[0049] The compositions of the present invention are used to form molded articles. Without wishing to impose any limitations, the term "for forming molded articles" indicates the ability to process the composition to obtain molded articles. Therefore, the phrase "for forming molded articles" is equivalent to "suitable for forming molded articles." Preferably, the compositions of the present invention are capable of providing molded articles by extrusion molding, more preferably by extrusion molding without a post-molding curing step.
[0050] The compositions of the present invention comprise (A) a thermoplastic binder phase, and (B) at least one material dispersed in the thermoplastic binder phase capable of reducing the dielectric constant and dielectric loss of the composition. The compositions of the present invention may also include other components besides components (A) and (B), but generally consist essentially of or comprise of components (A) and (B).
[0051] (B) The amount of material capable of reducing the dielectric constant and dielectric loss of the composition is 5% by weight or more relative to the total weight of the composition, the remainder of which may be formed of a thermoplastic binder phase.
[0052] (A) Thermoplastic adhesive phase The thermoplastic binder phase includes (A.1) one or more cyclic olefin copolymers and (A.2) thermoplastic materials other than cyclic olefin copolymers, and may optionally contain other components, such as additives, such as impact modifiers. The components and their amounts are described below.
[0053] (A.1) Cyclic olefin copolymers Cyclic olefin copolymers (COCs) are a class of thermoplastic polymers belonging to the cyclic olefin polymer (COP) family. Key properties of cyclic olefin copolymers include transparency; low birefringence; chemical resistance to acids, alkalis, and organic solvents; low water absorption; and high glass transition temperature (Tg). COCs can be processed using various manufacturing techniques, including injection molding, extrusion molding, and blow molding.
[0054] COPs are characterized by cyclic molecular structures in their repeating units, which form part of the polymer backbone and endow the polymer with unique properties. Therefore, COCs can be described as copolymers comprising repeating units derived from two or more different monomers as part of the polymer backbone, at least one of which is selected from cyclic olefins. Here, cyclic olefins include cyclic hydrocarbons containing at least one (i.e., at least one, but possibly two) carbon-carbon double bonds in their cyclic structure (typically in alicyclic hydrocarbon rings).
[0055] Therefore, the COC used in this invention is a copolymer derived from at least one cyclic olefin (A.1-1) and at least one monomer (A.1-2) that can copolymerize with the cyclic olefin (A.1-1).
[0056] In one embodiment, at least one cyclic olefin (A.1-1) may be selected from compounds represented by the following formulas 1, 2 and 3 and combinations thereof: Formula 1 Where R 1 R 2 R 3 and R 4 Each is independently selected from hydrogen; including 1 to 10, preferably 1 to 6, more preferably 1 to 4, and even more preferably 1 to 3 or 1 to 2 carbon atoms of hydrocarbon groups (saturated or unsaturated, and straight-chain, branched or cyclic); -(CH2)COOR 6 ;-(CH2) n OCOR 6 ;-(CH2)n OR 6 (CH2) n CN;-(CH2)CONR 7 R 8 ;where R 6 R 7 and R 8 Selected from hydrogen and hydrocarbon groups (saturated or unsaturated, and straight-chain, branched or cyclic) comprising 1 to 10 carbon atoms, 1 to 6 carbon atoms, 1 to 4 carbon atoms, or 1 to 3 carbon atoms or 1 to 2 carbon atoms, and n is 0, 1, 2, 3 or greater; and -(CH2). n R 9 , where R 9 For Si(R) 10 )R 11 , where R 10 R is a hydrocarbon group (saturated or unsaturated, straight or branched) comprising 1 to 10 carbon atoms, 1 to 6 carbon atoms, 1 to 4 carbon atoms, or 1 to 3 carbon atoms. 11 The halogen is preferred, either Cl or Br, and n and q are each 0, 1, 2, or 3 or greater. In equations 1 and 2 above, R 1 To R 8 The represented hydrocarbon group can be a straight-chain or branched alkyl group that is optionally substituted with one or more halogen (F, Cl, Br or I, preferably F, Cl or Br) groups. Formula 2 Where R 1 and R 4 As defined in Equation 1, and R 5 Selected from -CH2-, -O-, or -NR 6 -, where R 6 For hydrogen or as in Formula 1 for R 1 To R 4 Defined hydrocarbon group; Formula 3 Where R 1 and R 4 With respect to R in Equation 1 above 1 and R 4 Defined in the same manner, and preferably hydrogen or a hydrocarbon group having 1 to 10, preferably 1 to 6, more preferably 1 to 4 (e.g., 1 to 3, 1 or 2 or 1) carbon atoms, such as a straight-chain or branched alkyl group having 1 to 10, preferably 1 to 6, more preferably 1 to 4 (e.g., 1 to 3, 1 or 2 or 1) carbon atoms. In another preferred embodiment, R 1 and R 4Both contain hydrogen to provide cyclopentadiene.
[0057] In one embodiment, at least one cyclic olefin (A.1-1) may be selected from norbornene, dicyclopentadiene, 5-methyl-2-norbornene, 5-ethyl-2-norbornene, 5-ethylidene-2-norbornene, 5-propyl-2-norbornene, 5-butyl-2-norbornene, 5-pentyl-2-norbornene, 5-hexyl-2-norbornene, 5-cyclohexyl-2-norbornene, 5-heptyl-2-norbornene, 5-octyl-2-norbornene, 5-nonyl-2-norbornene, 5-decyl-2-norbornene, 5-ethylidene-5-chloro-2-norbornene, 5-propyl-5-chloro-2-norbornene, 5-butyl-5-chloro-2-norbornene, 5-pentyl-2-norbornene, 5-[unclear text - likely a continuum name or abbreviation] 5-Hexyl-5-chloro-2-norbornene, 5-cyclohexyl-5-chloro-2-norbornene, 5-heptyl-5-chloro-2-norbornene, 5-octyl-5-chloro-2-norbornene, 5-nonyl-5-chloro-2-norbornene, 5-decyl-5-chloro-2-norbornene, 5-methyl-5-bromo-2-norbornene, 5-ethylidene-5-bromo-2-norbornene, 5-propyl-5-bromo-2-norbornene, 5-butyl-5-bromo-2-norbornene, 5-pentyl-5-bromo-2-norbornene, 5-hexyl-5-bromo-2-norbornene, 5-cyclohexyl-5-bromo-2-norbornene, 5-heptyl-5-bromo-2-norbornene Borneol, 5-octyl-5-bromo-2-norbornol, 5-nonyl-5-bromo-2-norbornol, 5-decyl-5-bromo-2-norbornol, methyl 5-norbornol-2-carboxylate, ethyl 5-norbornol-2-carboxylate, phenyl 5-norbornol-2-carboxylate, methyl 2-methyl-5-norbornol-2-carboxylate, butyl 3-phenyl-5-norbornol-2-carboxylate, dimethyl 5-norbornol-2,3-dicarboxylate, cyclohexyl 5-norbornol-2-carboxylate, allyl 5-norbornol-2-carboxylate, acetic acid 5-norbornol-2-ol, 2,3-dimethyl-5-norbornol- 2,3-Dionitrile, 5-norbornen-2-carboxamide, N-methyl-5-norbornen-2-carboxamide, N,N-diethyl-5-norbornen-2-carboxamide, N,N,N',N'-tetramethyl-5-norbornen-2,3-dicarboxylic acid diamine, 5-chloro-2-norbornen, 5-bromo-2-norbornen, 5-fluoro-2-norbornen, 5-methyl-5-chloro-2-norbornen, 5-norbornen-2-carboxyethyl ester, 5-norbornen-2-carboxylic acid dibromopropyl ester, 5-norbornen-2-carboxylic acid dichloropropyl ester, 5-norbornen-2-carboxylic acid monochlorophenyl ester, 5-norbornen-2-carboxylic acid monobromophenyl ester, 5-norbornen-2-carboxylic acid tribromophenyl ester, 2,3-Dichloro-5-norbornene, 2-bromo-5-norbornene, 2-bromomethyl-5-norbornene, tribromobenzyl 5-norbornene-2-carboxylate, 5-norbornene-2,3-dicarboxylic anhydride, 2,3-dimethyl-5-norbornene-2,3-dicarboxylic anhydride, 5-norbornene-2,3-dicarboximide, phenyl-2-methyl-5-norbornene-2,3-dicarboximide, 2-trichlorosilyl-5-norbornene, 2-(dimethylmethoxysilyl)-5-norbornene, 2-(dimethylacetylsilyl)-5-norbornene, and 2-trimethylsilyl-5-norbornene.
[0058] In one embodiment, at least one cyclic olefin (A1.1) is composed of norbornene, which is R in Formula 1. 1 To R 4 All are compounds composed of hydrogen. In another embodiment, at least one cyclic olefin (A.1-1) is composed of (i.e., dicyclopentadiene).
[0059] In one embodiment, at least one cyclic olefin (A.1-1) is formed from a combination of norbornene and cyclopentadiene, or from a combination of one of norbornene and cyclopentadiene with one or more compounds of formulas 1 to 3 other than norbornene and dicyclopentadiene. In one embodiment, at least one cyclic olefin (A.1-1) may be formed from 85-95% by weight of norbornene and the remaining 5-15% by weight of dicyclopentadiene, or from 85-95% by weight of dicyclopentadiene and the remaining 5-15% by weight of norbornene.
[0060] The at least one monomer (A.1-2) that can copolymerize with the cyclic olefin (A.1-1) is not particularly limited, but is preferably an α-olefin with 2 to 20 carbon atoms, more preferably 2 to 12 carbon atoms, more preferably 2 to 8 carbon atoms, and most preferably 2 to 6 carbon atoms. In a preferred embodiment, the at least one monomer (A.1-2) that can copolymerize with the cyclic olefin (A.1-1) is at least one selected from ethylene, propylene, 1-butene, 1-hexene, and 1-octene, more preferably at least one selected from ethylene, propylene, 1-butene, and 1-hexene, and even more preferably at least one selected from ethylene, propylene, and 1-butene. Most preferably, the at least one monomer (A.1-2) that can copolymerize with the cyclic olefin (A.1-1) is ethylene, propylene, or a combination of ethylene and propylene.
[0061] There is no particular limitation on the relative amount of repeating units in COC derived from at least one cyclic olefin (A.1-1) and at least one monomer (A.1-2) copolymerizable with the cyclic olefin (A.1-1). In one embodiment, the molar percentage of repeating units derived from at least one cyclic olefin (A.1-1) is in the range of 10-80%, more preferably 15-65%, even more preferably 20-50%, and preferably the molar percentage of repeating units derived from at least one monomer (A.1-2) copolymerizable with the cyclic olefin (A.1-1) is 20-90%, more preferably 35-85%, even more preferably 50-80%, totaling 100% in each case. While these percentages relate to all repeating units derived from at least one cyclic olefin in (A.1-1) and (A.1-2), preferred embodiments of (A.1-1) and (A.1-2) also apply, such that at least one cyclic olefin in (A.1-1) can be formed from norbornene, dicyclopentadiene, or combinations thereof, preferably norbornene, and the copolymerizable monomer (A.1-2) can be selected from α-olefins, which are selected from ethylene, propylene, and 1-butene, preferably ethylene, propylene, or combinations thereof.
[0062] In a preferred embodiment, the cyclic olefin copolymer (A.1) is a copolymer composed of repeating units derived from ethylene and one or more cyclic olefins, wherein the cyclic olefin is preferably norbornene or a norbornene derivative, preferably 2-norbornene. Here, the content of norbornene or a norbornene derivative (preferably 2-norbornene) can be 45 mol% or more, preferably 50 mol% or more, of all repeating units of the ethylene-cyclic olefin copolymer, with the remainder formed from ethylene.
[0063] Therefore, a preferred example of a COC that can be used in this invention is a binary copolymer of ethylene and norbornene, as represented by Formula 4, which can generally be obtained by copolymerization in the presence of a metallocene catalyst: Formula 4 Where x and y represent the molar percentage of each repeating unit, x+y is 100% and both x and y are greater than 0. Although there are no particular restrictions on the values of x and y, x is preferably greater than 0, such as 1, 2, 3, 4 or 5, such as 10, up to 50, preferably up to 40, such as 10 to 40, and y is preferably 50 to less than 100, such as 50 to 95, such as 60 to 90.
[0064] COCs can be prepared by those skilled in the art using methods well known in the art. Alternatively, commercial products can be used. Examples of commercial products include Topas® (available from Polyplastics), Apel® (available from Mitsui Chemicals), Crystal Zenith® (available from Zeon Corporation), cyclic olefin copolymers available from Cyclics Corporation, and Arton® (available from JSR Corporation).
[0065] Therefore, suitable COC materials are readily available to those skilled in the art. Preferably, the COC meets one, two, or all three of the following requirements (MFR and density, MFR and Tg, or density and Tg): - Melt flow rate (MFR) (determined according to ASTM D1238 at a load of 2.16 kg): 0.1–100 g / 10 min, preferably 0.5 to 20 g / 10 min, more preferably 1.0 to 10 g / 10 min; - Density (determined according to ISO 1183): 0.95 to 1.15 g / cm³ 3 Preferably, the concentration is 0.98 to 1.05 g / cm³. 3 ; - Glass transition temperature Tg (determined according to ISO 11357-1): 100°C or higher, preferably 120°C or higher, more preferably 140°C or higher, even more preferably 145°C or higher, but generally 200°C or lower, preferably 180°C or lower.
[0066] (A.2) Thermoplastic materials other than cyclic olefin copolymers There are no particular restrictions on thermoplastic materials other than COC, as long as they can form a continuous phase with COC. Thermoplastic material (A.2) is formed from one or more polymers, none of which contain repeating units derived from monomers with olefinically unsaturated groups (such as norbornene or cyclopentadiene) that are part of a ring structure. Therefore, thermoplastic material (A.2) is structurally different from COC (A.1).
[0067] Although there are no particular limitations on the thermoplastic material (A.2), it is preferably selected from polyesters, polyolefins, especially homopolymers of ethylene, homopolymers of propylene, copolymers of ethylene and propylene, and copolymers of one or two of ethylene and propylene with other α-olefins, polyamides, polycarbonates, polystyrene, copolymers of styrene such as ABS, SAN and SB, acrylic polymers, polyethersulfone, polyetheretherketone, polyetherimide, polyphenylene ether, polyphenylene sulfide and melt-processed fluorinated polymers such as PVDF or PTFE.
[0068] The type and relative amount of thermoplastic materials other than COC can be selected by those skilled in the art based on the intended application and desired performance balance. In practice, polyolefins, polyesters, and polyamides have been found to provide a suitable performance balance. Polyesters, such as polyalkylene terephthalates (PBT) and PET (polyethylene terephthalate), have provided good results, particularly when laser welding of molded parts is desired; therefore, PBT and PET are preferred. When laser weldability is desired, combining ethylene- and norbornene-based COC with PBT has yielded particularly good results.
[0069] Suitable thermoplastic materials are well known to those skilled in the art and can be selected from general engineering plastics, many of which are commercially available. In particular, the types suitable for injection molding can be freely chosen, and the required properties are well known to those skilled in the art. Therefore, detailed descriptions of these materials and their manufacturing methods are omitted.
[0070] Composition of thermoplastic adhesive phase and optional additives The relative amounts of (A.1) one or more cyclic olefin copolymers and (A.2) thermoplastic materials other than cyclic olefin copolymers that form the thermoplastic binder phase (A) are such that the total amount of one or more cyclic olefin copolymers (A1.1) is 10 to 95% by weight, preferably 10 to 85% by weight, more preferably 15 to 75% by weight, even more preferably 15 to 60% by weight, and even more preferably 15 to 40% by weight.
[0071] The remainder of the binder phase is formed of (A.2) thermoplastic materials other than cyclic olefin copolymers and, optionally, other additives (e.g., one or more impact modifiers) as described below.
[0072] In one embodiment, 75% by weight or more, such as 80% by weight or more, 85% by weight or more, 90% by weight or more, such as 95% by weight or more, but 100% by weight or less, such as 98% by weight or less, of the thermoplastic binder phase is formed of (A.1) one or more cyclic olefin copolymers and (A.2) a thermoplastic material other than cyclic olefin copolymers. The portion of the thermoplastic binder phase (A) not formed of (A.1) one or more cyclic olefin copolymers and (A.2) a thermoplastic material other than cyclic olefin copolymers (if present) may be formed of impact modifiers and other optional components (e.g., plasticizers, flame retardants, colorants, processing aids, antistatic agents, release agents, heat stabilizers, and other additives known in the art).
[0073] The embodiment in which an impact modifier is present in the thermoplastic binder phase is particularly preferred in order to impart durability and other desired physical properties to the resulting molded article. The impact modifier may or may not have a core-shell structure. While impact modifiers known in the art can be used without limitation, preferably, the impact modifier can be selected from styrene block copolymers (SBCs), such as styrene-ethylene-butene-styrene block copolymers (SEBS), methyl methacrylate-butadiene-styrene (MBS), acrylonitrile-butadiene-styrene (ABS), acrylic impact modifiers (AIMs), such as acrylate-methyl acrylate copolymers, acrylonitrile-styrene-acrylate (ASA), ethylene-propylene-diene monomer (EPDM) copolymers, chlorinated polyethylene (CPE), ethylene-vinyl acetate copolymers (EVA), acrylonitrile-butadiene rubber (NBR), and maleic anhydride modified polymers such as maleic anhydride-grafted EPDM and maleic anhydride-grafted ethylene / C 3-12 α-olefin copolymers, ethylene-unsaturated epoxide copolymers, ethylene-carboxylic anhydride copolymers, polymers made from hydroxyl-functional monomers, including polymers comprising repeating units derived from (meth)acrylic acid hydroxy C2-6 alkyl esters; and combinations thereof.
[0074] Therefore, in embodiments where the thermoplastic material other than COC is selected from polyolefins, polyesters, and polyamides (preferably polyesters such as PET and PBT), the impact modifier is structurally different from these materials (A.2) and can be selected from the impact modifiers listed in the preceding paragraph, including SBCs such as SEBS. SBCs such as SEBS are particularly useful because they not only act as impact modifiers but also improve the compatibility between polyesters (e.g., PBT) and COC.
[0075] In one embodiment, the thermoplastic binder phase comprises, by weight percent relative to the total weight of the binder phase: Cyclic olefin copolymers 15 to 75, for example 20 to 70, or 35 to 65; Polyalkylene terephthalate 25 to 85, for example 30 to 80, or 35 to 65; Impact modifier 0 to 20, for example 5 to 15, or 10 to 15; These components are preferably 80% by weight or more of the total weight of the thermoplastic binder phase (A), for example, 85% or more, 90% or more, or 95% or more, but 100% or less, for example, 98% or less. Additionally, the polyalkylene terephthalate is preferably formed from PET and / or PBT, preferably from PBT only, and the impact modifier is preferably SBC, more preferably SEBS.
[0076] (B) Materials capable of reducing the dielectric constant and dielectric loss of the composition. In addition to the thermoplastic binder phase (A), the composition of the present invention also includes, as component (B), at least one material capable of reducing the dielectric constant and dielectric loss of the composition.
[0077] Here, by referring to a component as “capable of reducing dielectric constant and dielectric loss”, it means that a composition including component (B) has both a lower dielectric constant and a lower dielectric loss at 76.5 GHz than the same composition lacking component (B) (i.e., a thermoplastic binder phase in the case where the composition consists of components (A) and (B)).
[0078] Therefore, the presence of component (B) improves the performance of the composition, for example, when used to form radomes, as this can improve the potential operating range of radar equipment. At the same time, due to the presence of a specific binder phase, it is still possible to obtain molded parts that have the desired properties in use (reflected in tensile modulus, tensile strength, and elongation at break).
[0079] Furthermore, if the density of component (B) is lower than that of the binder phase, the presence of component (B) can result in a lower density of the composition compared to the binder phase (A) alone, which allows for weight reduction.
[0080] While there are no particular limitations on the properties of component (B), materials made of glass have been found to provide preferred results and allow for a desired balance of performance. Therefore, in one embodiment, the composition of this application comprises one or more of B.1 glass fibers; B.2 hollow glass spheres; and B.3 aerogel as component (B). Note that the density of the glass spheres and aerogel is generally lower than that of the binder phase, such that including these can result in a lower density relative to the binder phase as a whole.
[0081] Glass spheres and aerogel trap air and thus effectively reduce the dielectric constant, while glass fibers provide reinforcement. Therefore, the compositions of the present invention preferably include both B.1 glass fibers and B.2 hollow glass spheres. If used in combination, the weight ratio of the hollow glass spheres is preferably 25% or more, more preferably 50% or more, of the total weight of the glass fibers and glass spheres, to ensure a reduction in the overall density of the composition and to ensure low dielectric loss.
[0082] Glass spheres (also known as glass bubbles) can have any suitable size. In practice, the average diameter (determined by laser scattering as a volume-based D) is... 50 Materials with a particle size of 50 μm or smaller, such as 30 μm or smaller or 25 μm or smaller, but 1 μm or larger, such as 5 μm or larger or 10 μm or larger, have proven useful. Glass spheres preferably have an isostatic compressive strength of 100 MPa or higher, such as 130 MPa or higher, preferably 150 MPa or higher (determined by 3M QCM 14.1.8 method) to avoid breakage during processing. Within this range, large particle size D... 50 Because a larger space for trapped air can lead to a greater reduction in dielectric loss, while larger particles typically have lower isostatic compressive strength.
[0083] There are no particular limitations on the glass fibers, but they typically have a strand length (measured according to JISR 3420) of 0.5 mm or greater, preferably 1.0 mm or greater, for example 2.0 mm or greater, but typically 10.0 mm or less, preferably 8.0 mm or less. Fibers that are too long can result in a rough surface on the molded part and complicate the molding process, while fibers that are too short may fail to provide the desired reinforcement.
[0084] There are no particular limitations on the glass used to form glass fibers and / or glass spheres, and it can be selected from a wide range of materials, including C-glass, R-glass, D-glass, and E-glass, but E-glass is preferred. E-glass is known in the art to refer to aluminoborosilicate glass containing alumina (Al₂O₃), boron oxide (B₂O₃), and silicon dioxide (SiO₂). Such glasses are characterized by a dielectric constant of 6.5 or less at 1 MHz and / or a volume resistivity of 10 Ω·cm. 13 Up to 10 15• cm. E-glass typically contains 53-57 wt% SiO2, 12-15 wt% Al2O3, 5-8 wt% B2O3, 0-0.6 wt% F, 0-less than 1 wt% Na2O and K2O, up to 0.5 wt% Fe2O3, and a total of 22-26 wt% CaO and MgO. Such glass can be obtained, for example, from Sant-Gobain Vetrotex Deutschland GmbH.
[0085] Aerogels are highly porous materials exhibiting a combination of low density, high porosity, and unique physical properties. They consist of a gel in which the liquid component has been replaced by gas, resulting in a material composed almost entirely of air. Aerogels can have a porosity ranging from 0.001 to 0.200 g / cm³, for example, from 0.003 to 0.150 g / cm³. 3 Or 0.060 g / cm 3 Up to 0.130 g / cm 3 The bulk density. Bulk density is defined as the ratio of weight to volume, where weight can be expressed with a precision of 10-1. -5 The volume of aerogel can be measured using a microbalance with a g-scale, and geometric methods can be used to measure it.
[0086] Porosity can be 80% or higher, for example 90% or higher (e.g., determined by nitrogen adsorption via the BET method, using an ASAP 2020 instrument (Micromeritics, USA)). Before analysis, the sample can be degassed under vacuum at 150°C for at least 2 hours.
[0087] Aerogels can be made from a variety of materials, including silica, carbon, polymers, etc. A common method for producing aerogels involves generating a gel using a precursor material such as silica gel. The gel is then subjected to a process called supercritical drying, in which the liquid component is replaced by a gas, leaving a solid aerogel structure. Aerogels and their production methods are known to those skilled in the art. As an example, further information on the properties and synthesis of polyimide aerogels can be found in the scientific literature, as cited in US 9,073,759 B2 (see, for example, S, SS, Rai, N. & Chauhan, I. Multifunctional Aerogels: A comprehensive review on types, synthesis and applications of aerogels. J Sol-Gel Sci Technol 105, 324–336 (2023) and its cited references). Commercially available aerogel materials can also be used, such as Polyimide Aerogel Powder from Blueshift Materials, USA, traded under the name AeroZero.
[0088] There are no particular limitations on the aerogel, but it is preferably selected from silica aerogels and polymer aerogels, such as aerogels obtained from polyimide. The aerogel preferably has a porosity of 90% or greater.
[0089] In the composition for forming molded articles according to the present invention, the content of (B) at least one material capable of reducing dielectric constant and dielectric loss is 5% by weight or more relative to the total weight of the composition. If multiple materials that conform to (B) as materials capable of reducing dielectric constant and dielectric loss of the composition are used in combination, this refers to the total weight of all materials that conform to (B) as materials capable of reducing dielectric constant and dielectric loss of the composition. The content can be 6% by weight or more, 7% by weight or more, 8% by weight or more, 9% by weight or more, 10% by weight or more, 11% by weight or more, preferably 15% by weight or more, for example 20% by weight or more (e.g., 21% by weight or more) in order to enhance the effects of the various materials as explained above. However, if the amount of (B) at least one material capable of reducing dielectric constant is too high, cohesion and moldability may be compromised. Therefore, the upper limit of the total content of (B) at least one material capable of reducing dielectric constant is generally 35% by weight or less, preferably 30% by weight or less, for example 25% by weight or less.
[0090] Therefore, in one embodiment, the composition of the present invention for forming a molded article comprises 30% by weight or less of (B) at least one material capable of reducing dielectric constant and dielectric loss and 70% by weight or more of a thermoplastic binder phase (B), and the total amount of (A) and (B) forms 90% by weight or more, preferably 95% by weight or more, for example 100% by weight of the composition.
[0091] Performance and advantages of compositions used to form molded articles By appropriately selecting and combining materials as described above, a composition for forming molded articles (e.g., radomes) can be obtained that surpasses existing compositions by providing reduced dielectric loss and a lower dielectric constant, thus paving the way for increased operating range in radar equipment (e.g., used in the automotive industry). Simultaneously, appropriate selection of components allows for lower densities than conventional materials, contributing to weight reduction and improved fuel economy. Furthermore, the composition for forming molded articles of this application can be readily processed using techniques such as laser welding, and also allows for physical properties such as tensile modulus, tensile strength, impact resistance, or elongation at break, which, while not necessarily superior to currently used materials, still meet current requirements, for example, in the automotive industry. Moreover, warping of the molded article can be suppressed or completely avoided.
[0092] By appropriately selecting materials and quantities, the present invention allows for the preparation of compositions that can be used to form molded articles having one, two, three, four, five, or all six of the following properties a and f: a. Dielectric constant (dk) (@76.5 GHz) according to VDM 288 (09 / 2023): 3.50 or less, preferably 3.20 or less, more preferably 3.00 or less, such as 2.90 or less, 2.85 or less, or 2.80 or less, most preferably 2.70 or less, such as 2.65 or less, 2.60 or less, or 2.57 or less. Although there is no particular limitation on the lower limit, the dielectric constant is generally 2.50 or higher.
[0093] b. Dielectric loss (df) (@76.5 GHz) according to VDM 288 (09 / 2023): 0.014 or less, e.g., 0.013 or less, 0.012 or less, or 0.11 or less, preferably 0.10 or less, e.g., 0.09 or less, more preferably 0.08 or less, or 0.07 or less, e.g., 0.05 or less, or 0.04 or less. While there is no particular limitation on the lower limit, it can be 0.01 or greater, e.g., 0.02 or greater, or 0.03 or greater.
[0094] c. Density according to ISO 1183-1: 1.35 g / cm³3 Or even smaller, for example, 1.30 g / cm³ 3 Or smaller or 1.25 g / cm³ 3 Or smaller, preferably 1.20 g / cm 3 Or smaller, more preferably 1.15 g / cm 3 Or smaller, with an optimal value of 1.10 g / cm³ 3 Or even less. While there is no lower limit to the density, it is typically 1.00 g / cm³. 3 Or larger.
[0095] d. Elongation at break, measured on an injection-molded Type 1A test bar according to ISO 527 1 / 2: 3.5% or higher, such as 3.7% or higher, 3.8% or higher, or 4.0% or higher, but typically 7.0% or less, such as 6% or less, such as 5.5% or less.
[0096] e. Tensile strength at break (in MPa) determined on an injection-molded Type 1A test bar according to ISO 527 1 / 2: 40 or higher, for example 45 or higher, preferably 50 or higher, but typically 110 or lower, for example 100 or lower or 90 or lower, for example 70 or lower.
[0097] f. Tensile modulus (in MPa) determined on an injection-molded Type 1A test bar according to ISO 527 1 / 2: 1,000 or greater, for example 1,500 or greater, for example 1,800 or greater, but typically 5,000 or less, for example 4,000 or less.
[0098] Molded products The molded articles obtainable from the compositions of the present invention can take virtually any form, but are preferably molded articles for applications requiring low dielectric loss. This includes housings for any type of electrical and electronic equipment, such as those that emit and / or receive radiation in the range of 5 MHz to 130 GHz. In addition to radomes for vehicles such as cars and trucks, this includes mobile communication devices, such as devices utilizing 5G networks, or electronic devices designed to connect to Wi-Fi networks. Therefore, the molded articles of the present invention include not only radomes, but also covers and housings for components such as mobile phones, tablets, laptops, desktop computers, printers, scanners, remote controls, transmission towers, Wi-Fi transmission devices, routers, Wi-Fi repeaters, and game consoles.
[0099] Method for producing molded articles There are no particular limitations on the methods used to produce the molded articles, and they can be freely chosen by those skilled in the art. However, given the properties of the compositions of the present invention and in order to improve productivity and reduce production costs, the molded articles are preferably formed by techniques involving extrusion molding and / or laser welding. Conditions can be appropriately selected by those skilled in the art based on common knowledge and the guidance in the following examples.
[0100] Example The present invention will be further illustrated by the following embodiments, but the present invention is not limited thereto.
[0101] The following components were used in the examples: Component A.1: Topas · 6015S (available from Topas Advanced Polymers GmbH, Germany), a COC based on ethylene and norbornene, suitable for injection molding, with a density of 1.02 g / cm³. 3 The melt volumetric flow rate (MVR) at 260℃ and 2.16 kg load is 4 cm. 3 / 10 minutes, the glass transition temperature is 158℃, and the light transmittance is 91.9%.
[0102] Component A.2: Dinadur·PBT1SO1 HI-0022: a commercially available impact-modified polybutylene terephthalate, derived from Nordmann Rassmann (Germany); density 1.22 g / cm³. 3 Suitable for injection molding (high MFR grade). Ultradur B4520, a PBT available from BASF, without impact modification. Component B: Glass fiber: Nitto Boseki CN 3J-256 8482, filament length 3.0 mm Glass microspheres: iM30K 8482; high-strength glass microspheres, available from 3M, average particle size: 18 μm, isostatic compressive strength 193 MPa. Impact modifier: Kraton MD6951MS, a styrene-ethylene / butene block copolymer with 34% polystyrene content and an MFR (2.16 kg, 230°C, according to ASTM D 1238) of 36 ≤ 50, available from Kraton Corporation. The following materials were used as comparison materials: Ultradur B 4300 G4 PBT, with 20% glass fiber content, available from BASF, has an MVR of 16 cm⁻¹ at 250°C and a load of 2.16 kg. 3 / 10 minutes, suitable for injection molding and used to manufacture, for example, connectors and small automotive parts.
[0103] Preperm® is available from Premix (part of Avient Corporation) and is marketed for use in the production of components for high-frequency applications, such as antenna housings, due to its low dielectric loss. The exact composition of this commercial material is not disclosed.
[0104] Comparative Examples 1 and 2 and Examples 1-4 Components (A.1) and (A.2) shown in Table 1 below were mixed to prepare a compound and injection molded. The composition was prepared during the extrusion process using an 8-zone co-rotating 24 mm twin-screw extruder. A dry blend of impact-modified PBT / COC resin was prepared and fed into the extruder via the hopper in zone 1. The screw speed was set to 300 rpm, with a corresponding screw torque of 30 Nm. The temperature was set to 270°C to melt the resin. Material (B) was added in zone 7 via a gravity-side feed unit with a screw speed set to 100 rpm. During compounding, a pressure of approximately 26 bar was reached.
[0105] Table 1: Composition of Comparative Examples (CE) 1 and 2 and Examples (Ex) 1-4 The prepared compound was injection molded to produce ISO 1A test bars and sheets for mechanical and dielectric testing. For the final application, the compound was also injection molded to form a radome.
[0106] In the above examples and comparative examples, PBT and COC were used in ratios of 3:2 and opposite ratios, and blended with glass beads and glass fibers as shown. The content of glass beads and glass fibers used was evaluated in the range of 0-10% by weight. Based on the observed undesirable warping effect, the compositions obtained in Examples 1 and 3 were not selected for further testing. This result indicates that an amount of component (B) greater than 15% is preferably used to reduce warping.
[0107] Comparative Example 5 Molded articles were obtained in the same manner as Comparative Examples 1 and 2 and Example 1 8211; 4, except that the commercially available product Ultradur B4300 G4 was used without adding any additional components (BASF product, PBT only and 20% glass fiber by weight, no COC).
[0108] The obtained test pieces were evaluated in the same manner as described above. The results are shown in Table 2: Table 2: Test Results *dk measured at 1 MHz A comparison between Comparative Example 1 and Example 2 (which relied on the same binder phase, differing only in the presence / absence of component B) shows that component B can reduce density and dielectric constant dk. Furthermore, component (B) can increase tensile modulus and tensile strength, resulting in a more durable material suitable for practical applications. The same trend is observed between Comparative Example 2 and Example 4. This demonstrates that, using the composition as claimed, a desired balance of performance—a combination of low dielectric constant and low density—can be achieved while simultaneously obtaining satisfactory tensile properties for practical use.
[0109] Incidentally, all compositions relying on the combination of COC and thermoplastic materials as the binder phase exhibited superior dielectric loss and density compared to the commercially available product used in Comparative Example 5.
[0110] Examples 5 to 8 and Comparative Examples 6 and 7 Laser weldability was evaluated on the compositions obtained in Examples 1-4, but the transparency of the commercially available impact-modified PBT TDINadur·PBT1SO1 HI-0022 was found to be too low, at only 3%. Therefore, this compound was replaced with the non-impact-modified PBT Ultradur·B4520 (BASF), which was compounded with the impact modifier Kraton MD6951. The compositions listed in Table 3 were prepared and used to injection mold test pieces in the same manner as described above. Additionally, test pieces were formed from the commercially available product Preperm· (available from Avient Corporation) and evaluated in the same manner.
[0111] Table 3: Composition of Comparative Examples (CE) 6 and 7 and Examples (Ex) 5-8 The results are shown in Table 4: Table 4: Test Results *dk measured at 1 MHz Of the above Examples 5 & 8, only Examples 5 and 6 were found to be laser-weldable. This is because in Examples 7 and 8, the relative amount of COC was too high (or the amount of PBT was too low) to achieve laser weldability. Therefore, Example 5 combines very low loss with laser weldability and good mechanical properties.
[0112] Furthermore, the above experiments show that the dielectric loss of the composition of the present invention is lower than that of commercially available Preperm, while exhibiting similarly good performance for practical use, such as impact resistance.
Claims
1. A composition for forming a molded article, comprising: A thermoplastic adhesive phase, and, dispersed in the thermoplastic adhesive phase B. At least one material capable of reducing the dielectric constant and dielectric loss of the composition. The thermoplastic adhesive phase comprises at least: A.1 One or more cyclic olefin copolymers, and A.2 Thermoplastic materials other than cyclic olefin copolymers, preferably selected from polyesters, polyolefins, especially homopolymers of ethylene, homopolymers of propylene, copolymers of ethylene and propylene, copolymers of one or two of ethylene and propylene with other α-olefins, polyamides, polycarbonates, polystyrene, copolymers of styrene such as ABS, SAN and SB, acrylic polymers, polyethersulfone, polyetheretherketone, polyetherimide, polyphenylene ether, polyphenylene sulfide, and melt-processed fluorinated polymers such as PVDF or PTFE. Wherein, the amount of the material described in B that can reduce the dielectric constant and dielectric loss of the composition is 5% by weight or more relative to the total weight of the composition, and The total amount of the one or more cyclic olefin copolymers is 10 to 95% by weight of the total weight of the thermoplastic adhesive phase A.
2. The composition for forming a molded article according to claim 1, wherein the material B capable of reducing the dielectric constant and dielectric loss of the composition comprises one or more of the following: B.1 Glass fiber; B.2 Hollow glass spheres; and B.3 Aerogel; And preferably includes both B.1 glass fiber and B.2 hollow glass spheres.
3. The composition for forming a molded article according to claim 1 or 2, wherein the thermoplastic binder phase comprises, in addition to components A.1 and A.2, [further details needed]. A.3 One or more impact modifiers having or not having a core-shell structure, preferably selected from styrene block copolymers (SBCs), such as styrene-ethylene-butene-styrene block copolymers (SEBS), methyl methacrylate-butadiene-styrene (MBS), acrylonitrile-butadiene-styrene (ABS); acrylic impact modifiers (AIMs), such as acrylate-methacrylate copolymers, acrylonitrile-styrene-acrylates (ASA), ethylene-propylene-diene monomer (EPDM) copolymers, chlorinated polyethylene (CPE), ethylene-vinyl acetate copolymers (EVA), acrylonitrile-butadiene rubber (NBR), maleic anhydride modified polymers such as maleic anhydride-grafted EPDM and maleic anhydride-grafted ethylene / C3-12 α-olefin copolymers, ethylene-unsaturated epoxide copolymers, ethylene-carboxylic anhydride copolymers, polymers made from hydroxyl-functional monomers, such as polymers comprising repeating units derived from (meth)acrylate hydroxyl C2-6 alkyl esters; and combinations thereof; The impact modifier is present in an amount of 0.1 to 10% by weight of the total weight of the thermoplastic adhesive phase A.
4. The composition for forming a molded article according to claim 1, 2 or 3, wherein the composition satisfies one or more of the following: (a) Density: 1.30 g / cm³ 3 or smaller (b) Dielectric constant at 76.5 GHz: 2.58 or less (c) Dielectric loss at 76.5 GHz: 0.01 or less (d) Transmittance at 980 nm: 8% or more.
5. The composition for forming a molded article according to any one of claims 1 to 4, wherein the thermoplastic material other than the cyclic olefin copolymer in A.2 is selected from polyolefins and polyesters, wherein the polyester is preferably polyalkylene terephthalate, more preferably polybutylene terephthalate, and wherein preferably, the thermoplastic material other than the cyclic olefin copolymer selected from polyolefins and polyesters is present in an amount of 30 to 65% by weight of the total composition.
6. The composition for forming a molded article according to any one of claims 1 to 5, wherein the amount of the cyclic olefin copolymer is 10 to 85% by weight of the total composition, preferably 15 to 60% by weight.
7. The composition for forming a molded article according to any one of claims 1 to 6, wherein the cyclic olefin copolymer is a copolymer composed of repeating units derived from ethylene and one or more cyclic olefins, wherein the cyclic olefin is preferably norbornene or a norbornene derivative, preferably 2-norbornene.
8. The composition for forming a molded article according to claim 7, wherein the content of norbornene or a norbornene derivative, preferably 2-norbornene, is 45 mol% or more, preferably 50 mol% or more, of all repeating units of the copolymer of ethylene and cyclic olefins.
9. The composition for forming a molded article according to any one of claims 1 to 8, comprising glass fiber and hollow glass spheres as component B, and satisfying the following relative amounts of components in weight % relative to the total weight of the composition: A thermoplastic adhesive phase of 60 to 90, preferably 70 to 80. B.1 Glass fiber 5 to 20, preferably 10 to 15 B.2 Hollow glass spheres: 5 to 20, preferably 10 to 15.
10. The composition for forming a molded article according to claim 9, wherein, The thermoplastic adhesive phase comprises, by weight percent relative to the total weight of the adhesive phase: A.1 Cyclic olefin copolymers 15 to 75 A.2 Polyalkylene terephthalate 25 to 85 A.3 Impact modifier 0 to 20.
11. The composition for forming a molded article according to any one of claims 1 to 7, wherein component B comprises B.3 one or more aerogels, wherein the aerogel is preferably selected from silica and polymer aerogels, such as aerogels obtained from polyimide, and / or wherein the aerogel preferably has a porosity of 90% or greater.
12. The composition for forming a molded article according to any one of claims 1 to 11, wherein the glass forming the glass fibers and / or hollow glass spheres has a dielectric constant of 6.5 (at 1 MHz) or less.
13. The composition for forming a molded article according to any one of claims 1 to 12, wherein A.1 is a cyclic olefin copolymer based on ethylene and norbornene. A.2 is polybutylene terephthalate, and B represents glass fiber and hollow glass spheres.
14. The composition for forming a molded article according to any one of claims 1 to 13, The thermoplastic adhesive phase includes A.1 and A.2, and optionally includes A.
3. A.1 is a cyclic olefin copolymer based on ethylene and norbornene. A.2 is polybutylene terephthalate, and A.3 is an impact modifier. B is made of glass fiber and hollow glass spheres, and in The amounts of A.1, A.2, and A.3, expressed as a percentage by weight relative to the total weight of the adhesive phase, are as follows: A.1 is 15 to 75% by weight. A.2 is 25 to 85% by weight, and A.3 is 0 to 20% by weight, and The amount of material B, which can reduce the dielectric constant and dielectric loss of the composition, is 15 to 20% by weight or more relative to the total weight of the composition.
15. A molded part that can be obtained from the composition according to any one of claims 1 to 14.
16. The molded part according to claim 15, which is an antenna radome or housing for an electronic device, preferably a device for emitting and / or receiving radiation in the range of 5 MHz to 130 GHz.
17. The molded part of claim 16, wherein the radome or housing is part of a radar device for a vehicle, preferably an automobile or truck.
18. A method for manufacturing a molded part according to claim 15 or 16, comprising processing the composition according to any one of claims 1 to 12 by extrusion molding and / or laser welding.
19. Use of the composition as defined in any one of claims 1 to 14 for manufacturing a housing or radome of an electronic device, wherein the electronic device is preferably a device for emitting and / or receiving radiation in the range of 5 MHz to 130 GHz, more preferably a radar device.
20. An electrical or electronic device for emitting and / or receiving electromagnetic radiation in the range of 5 MHz to 130 GHz, said device comprising a housing or radome made of a composition as defined in any one of claims 1 to 12, or a molded part as described in claim 15 or 16.
21. The electrical or electronic device according to claim 20, wherein it is a radar device for a vehicle, preferably an automobile or truck.
Citation Information
Patent Citations
Silica aerogels and their preparation
US9073759B2
Method and device for milking animals
WO2001074146A1
Radome fabrication using cyclic olefin resin in liquid molding
WO2018151800A2